Clinical features of post‐polypectomy bleeding associated with heparin bridge therapy. Issue 2 (4th June 2013) - Inoue, Takuya; Nishida, Tsutomu; Maekawa, Akira; Tsujii, Yoshiki; Akasaka, Tomofumi; Kato, Motohiko; Hayashi, Yoshito; Yamamoto, Shunsuke; Kondo, Jumpei; Yamada, Takuya; Shinzaki, Shinichiro; Iijima, Hideki; et al.
<x xml:space="preserve">Abstract</x> Background Heparin is given to patients undergoing colonoscopic polypectomy at high risk for thromboembolism. Little is known, however, about how heparin bridge therapy (HB) affects post‐polypectomy bleeding (PPB). The present study aimed to identify the clinical features of PPB associated with HB. Patients and Methods Data of consecutive inpatients who underwent colonoscopic polypectomy with antithrombotic therapy at Osaka University Hospital were retrospectively collected and categorized into a HB group or a non‐HB group. The incidence and characteristics of PPB were analyzed. Results A total of 117 patients with 279 lesions were identified, and the HB group included 45 patients. Nine of 10 patients with PPB were in the HB group, and the incidence of PPB was significantly higher in the HB group than in the non‐HB group (20.0% vs 1.4%, respectively). PPB onset was later in the HB group than inthe non‐HB group (median postoperative day: 4 vs 1, respectively). Five of the nine patients with PPB (55.6%) in the HB group experienced recurrent bleeding. One patient in the HB group required a blood transfusion as a result of massive PPB. All bleeding was eventually controlled endoscopically. Hospitalization was significantly longer in the HB group than in the non‐HB group (median hospitalization: 14 vs 4 days, respectively). The univariate analysis showed that the predictors of PPB were warfarin use, HB and pedunculated polyps. Conclusions PPB associated with HB is characterized by high incidence, late onset and recurrent bleeding, resulting in long hospitalization.